Better call Saul. Season one [videorecording (DVD)]. - Odenkirk, Bob, 1962-; Banks, Jonathan, 1947-; Seehorn, Rhea, 1972- (Sony Pictures Home Entertainment, 2015)
The television series is a spinoff from the popular Breaking Bad television show. The series takes place six years before the events of Breaking Bad and features small-time lawyer Jimmy McGill. The series follows the exploits of Jimmy and the circumstances that lead to his metamorphosis into criminal-minded lawyer Saul Goodman.